Pancreaticoduodenectomy performed for a patient with prepancreatic postduodenal portal vein: a case report and literature review - Tang, Bingjun; Li, Sijia; Wang, Pengfei; Ma, Jiming; Yu, Fei; Shi, Jun; Wang, Xuedong (Frontiers in Medicine, 2023)
Introduction Prepancreatic postduodenal portal vein (PPPV) is a rare congenital variation, with only 17 cases reported in the literature and five of them undergoing pancreaticoduodenectomy (PD). Of these, four were L-shaped PPPV with a thin wall that was difficult to isolate, while only one normal-shaped PPPV was reported previously. For patients undergoing PD, recognizing this variation is important to prevent PPPV injury, which could lead to liver ischemia or intraoperative hemorrhage. We here present a case of normal-shaped PPPV who underwent PD. Case presentation A 68-year-old woman underwent PD for bile duct carcinoma at our hospital. Preoperative enhanced CT revealed that the portal vein was located anterior to the pancreas and posterior to the duodenum, and the L-shaped splenic vein was longitudinally located posterior to the pancreatic neck. During surgery, there was a loose tissue area between the PPPV and the pancreatic head, and the PPPV could be isolated safely. The morphology of PPPV was similar to normal portal vein. Due to the presence of the PPPV, a superior mesenteric artery (SMA)-first approach from the anterior was at high risk of vascular injury, and the pancreatic neck could not be dissected at the dorsal face of PV. Therefore, the SMA was revealed by the classic right posterior approach after transection of the pancreatic neck on the dorsal surface of L-shaped spleen vein, and the specimen was successfully resected without significant intraoperative bleeding. The patient was discharged 18 days after surgery without complications. The final pathology was bile duct carcinoma with R0 resection. Conclusion PPPV is a rare variant that can be diagnosed by preoperative imaging. In PD procedure, knowledge of PPPV helps in surgical decision-making, approach selection and avoid major bleeding due to PPPV injury. The origin of normal-shaped and L-shaped PPPV might be different. Normal-shaped PPPV can be safely isolated in this case.